1982
DOI: 10.4153/cjm-1982-078-8
|View full text |Cite
|
Sign up to set email alerts
|

Locally Compact Normal Spaces in the Constructible Universe

Abstract: Arhangel'skiĭ proved around 1959 [1] that, for the class of perfectly normal locally compact spaces, metacompactness and paracompactness are equivalent. It is shown to be consistent that this equivalence holds for the (larger) class of normal locally compact spaces (answering a question of Tall [8], [9]).The consistency of the existence of locally compact normal noncollectionwise Hausdorff spaces has been known since 1967. It is shown that the existence of such spaces is independent of the axioms of set theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 5 publications
2
24
0
Order By: Relevance
“…In Cohen's original model for the negation of the Continuum Hypothesis (CH), and indeed in any model obtained by adding ℵ 2 Cohen reals to a model of ZFC, every locally compact normal space is ℵ 1 -cwH. This well-known fact can be shown by applying the proof technique of [W,Theorem 3] to [DTW,Theorem 1.4].…”
Section: Definition Let κ Be a Cardinal Number A Space X Is Weakly mentioning
confidence: 79%
“…In Cohen's original model for the negation of the Continuum Hypothesis (CH), and indeed in any model obtained by adding ℵ 2 Cohen reals to a model of ZFC, every locally compact normal space is ℵ 1 -cwH. This well-known fact can be shown by applying the proof technique of [W,Theorem 3] to [DTW,Theorem 1.4].…”
Section: Definition Let κ Be a Cardinal Number A Space X Is Weakly mentioning
confidence: 79%
“…[Wat82] showed that V = L yielded an affirmative answer. By a difficult forcing argument, a consistent counterexample was constructed by Gruenhage and Koszmider [GK96a].…”
Section: Normality Versus Collectionwise Hausdorffnessmentioning
confidence: 99%
“…In [15], we used Lemma 1 of this section to show that, under V = L, locally compact normal spaces are collectionwise Hausdorff and that, under V -L, locally compact, metacompact normal spaces are paracompact.…”
mentioning
confidence: 99%